Thermo-hydraulic Performance of Double-cut and Perforated Twisted Tape Based on Constant Surface Area - Naufal Faizurrahman Siregar; Damora Rhakasywi; Nicky Yongkimandalan (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
Improving the heat transfer of the heat exchanger pipe needs to be done. Inserting twisted tapes is often applied because it increases the Nusselt number, but it causes excessive pressure drop. This study investigates three variations of twisted tape, namely: plain, semicircular double cut, and circular perforation. The research gap concerns reducing the surface area of the twisted tape to the same area. Simulation using ANSYS Fluent. Variation analysis shows the Nusselt number increased by 36.64% for smooth, 40.94% for double semicircular cuts, and 36.95% for circular perforations. The friction factor increased by 232.26%, 253.46%, and 239.96%, respectively. The PEC value for each variation below 1 indicates a decrease in efficiency after the addition of the twisted tape. However, this study concludes that the double cut has the highest efficiency compared to other variations for the Reynolds number range of 6000 to 17000.